PERILAKU BELANJA PETANI TEMBAKAU PASCA PANEN RAYA DAN IMPLIKASINYA TERHADAP KETAHANAN EKONOMI KELUARGA (Study Di Desa Campur Sari, Kecamatan Bulu, Kabupaten Temanggung, Propinsi Jawa Tengah) - Setiawan, Deny (Jurnal Ketahanan Nasional, 2015)
This study was conducted to determined the effect of Farmer Behavior in spending money Post Harvest Tobacco toward the economic resilience viewpoint tobacco farmers in it. This research was a fi eld and descriptive. The study population was a tobacco farmer in the village environment Campursari which was only 3 miles from the Temanggung city center. The technique of sampling used purposive sampling method with the assumption that the population was bound by the context of a specific event, while taking a sample of 50 farmers. Data was collected through observation, interviews, and literature. Data was processed and analyzed by inductively qualitative and quantitative descriptive. The family economic resilience was measured based on the well-being of families, using the concept of the World Bankâs poverty income approach and the expenditure approach the Biro Pusat Statistik. Based on research, the existence of Harvest Tobacco on tobacco farming had a major role for the economy of farming families, including: (i) provide accessibility productive arena that carried the values of equality; (ii) be a leading contributor to the economy of farming families indicated by the high value of the contribution of revenue from the arena to the household income; (iii) the existence of tobacco farming capable of be an alternative option for the people of the informal sector employment Temanggung. While constraints in the management of tobacco farming included weather problems, tobacco regulation and innovation. The results also suggested that the behavior of farmers in post-harvest spend money tobacco implicated in the negative trend of economic resilience of farming families. The âpoorâ during the harvest respondents viewed from revenues of 2% and the respondents in the category of âpoorâ increased reach a percentage of 4% from the perspective of the poverty line approach to value consumption / expenditure. The conclusion of this study was the existence of Harvest tobacco had a great signifi cance for the economic improvement of farming families who could view how the farmers put a high dependence on the market arenas forthe fulfillment of The family welfare. However, the success of the harvest always followed by spending behavior that affected the economic resilience of the family.Keywords: Behavior, Harvest, and Family Economical Resilience